Yttrium and aluminum catalysts and model complexes for ring-opening polymerization of lactide and beta-butyrolactone - Klitzke, Joice Sandra (2013)
A series of new Al(III) complexes bearing silyl ortho-substituted 2,6- bis(naphtholate)-pyridine tridentate ligands ({ONOSiR3}2-, SiR3 = SiPh3, SiMe2tBu) and two monomeric Y(III) complexes bearing a new cumyl ortho-substituted 2,6- bis(phenolate)-pyridine tridentate ligand {ONOMe,Cumyl}2- have been prepared and structurally characterized in solution and in the solid-state. Preliminary studies on the catalytic performances of the compounds in the ROP of racemic lactide and β- butyrolactone are described. Also, details of the reactions of chiral Al-lactate and -{β- alkoxy ester} complexes which are close models/mimics of the first intermediates and active species involved in the initiation and propagation steps of the ROP of lactides and β-lactones with stoichiometric amounts of lactide.